2019
DOI: 10.1029/2018gl081109
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Global Contiguous SIF of OCO‐2

Abstract: The Orbiting Carbon Observatory‐2 (OCO‐2) collects solar‐induced chlorophyll fluorescence (SIF) at high spatial resolution along orbits ( trueSIF¯oco2_orbit), but its discontinuous spatial coverage precludes its full potential for understanding the mechanistic SIF‐photosynthesis relationship. This study developed a spatially contiguous global OCO‐2 SIF product at 0.05° and 16‐day resolutions ( trueSIF¯oco2_005) using machine learning constrained by physiological understandings. This was achieved by stratifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 44 publications
0
68
1
Order By: Relevance
“…With growing interests in satellite SIF, more satellite products at regional to global scale will become available such as TROPOMI SIF product with a global coverage . Future study can also take advantage of satellite SIF products extracted from satellite observation models such as high-resolution global contiguous Orbiting Carbon Observatory-2-based SIF product (Yu et al, 2018). In this study, we compared the original GOME-2 SIF product and downscaled high spatial resolution GOME-2 SIF product by Duveiller and Cescatti (2016); they showed a similar pattern when correlated to the meteorological drought indices ( Figures S7-S9).…”
Section: Potential Use Of Satellite Sif To Study Vegetation Response mentioning
confidence: 81%
“…With growing interests in satellite SIF, more satellite products at regional to global scale will become available such as TROPOMI SIF product with a global coverage . Future study can also take advantage of satellite SIF products extracted from satellite observation models such as high-resolution global contiguous Orbiting Carbon Observatory-2-based SIF product (Yu et al, 2018). In this study, we compared the original GOME-2 SIF product and downscaled high spatial resolution GOME-2 SIF product by Duveiller and Cescatti (2016); they showed a similar pattern when correlated to the meteorological drought indices ( Figures S7-S9).…”
Section: Potential Use Of Satellite Sif To Study Vegetation Response mentioning
confidence: 81%
“…Achieving this will require higher spatial and temporal resolution SIF with less noise. Yu et al () reported that trueSIF¯ OCO2_005 tended to underpredict high values and overpredict low values of SIF although the mean value was well predicted for shrubland. This may have resulted from the lower magnitude of SIF and thus higher impact of SIF retrieval noise in shrublands.…”
Section: Resultsmentioning
confidence: 97%
“…We utilized both the native OCO‐2 SIF (Sun et al, ) and spatially contiguous SIF products ( trueSIF¯ OCO2_005 ) at 0.05° and 16‐day resolution gap‐filled from OCO‐2 by Yu et al (), available since September 2014. OCO‐2 SIF was retrieved at both 757 and 771 nm using solar Fraunhofer lines.…”
Section: Data Sets and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, one possible solution for estimating crop yield using SIF data is to downscale satellite SIF data. For example, several studies have proposed methods to produce spatially continuous high spatial resolution SIF datasets using OCO-2 SIF measurements [95][96][97]. It is worthy of investigating the applicability of such downscaled SIF in estimating crop yields.…”
Section: Discussionmentioning
confidence: 99%